Clinical analysis on the influencing factors related to preterm twin pregnancy - Du,Lijuan (2022)
SUMMARY OBJECTIVE: The aim of this study was to explore the influencing factors of preterm twin pregnancy. METHODS: In total, 602 twin-pregnant women delivered from February 2016 to February 2020 were analyzed retrospectively. According to whether the pregnant women were preterm or not, they were divided into preterm group (n=363) and term group (n=239). Baseline information, such as maternal age, address, and education level of the pregnant women, were collected. The clinical information of pregnant women, such as chorionic, preeclampsia, gestational diabetes, premature rupture of membranes, abnormal fetal position, and fetal weight, were analyzed. Logistic regression analysis was used to analyze the risk factors. p-value <0.05 was considered statistically significant. RESULTS: In the preterm group, monochorionic diamniotic comorbidities were significantly higher compared with the control group (p<0.05). Higher risks of preterm group have lower education (p<0.05). Multiple logistic regression analysis demonstrated that education, preeclampsia, and premature rupture of membranes were risk factors for preterm twin pregnancy. CONCLUSIONS: Preterm birth in twin pregnancy is associated with many risk factors, such as education, preeclampsia, and premature rupture of membranes. Pregnancy supervision and prenatal guidance for twin pregnancy should be strengthened. Furthermore, early detection and diagnosis of comorbidities can improve maternal and neonatal outcomes.